Factors associated with job satisfaction among officers in an agricultural research institution - Che Jaafar, Nazirah (2018)
This study was conducted to identify the job satisfaction level amongst officers in an agricultural research institution. The specific objectives of this study were: 1) To determine the job satisfaction level, knowledge, attitude, skills, social demographics, and job factors of officers; 2) To determine the significance of the relationship between job satisfaction and social demographics, knowledge, attitude, skills, and job factors; and 3) To determine the determinant between social demographics, knowledge, attitude, skills, and job factors towards job satisfaction of officers. Therefore, a questionnaire was used to collect the study data. The census method has been used to obtain respondents since the total population of respondents was only 254. SPSS version 21.0 was used to analyse the data. This study found that 77.2% of respondents had high job satisfaction level and 22.8% had moderate job satisfaction level. This indicated that the job satisfaction level amongst officers in an agricultural research institution was high. This study also found that there was a positive and significant relationship at level of significance of 0.01 between job satisfaction and selected independent variables, namely salary (r = .509), promotion opportunities (r = .629), supervision (r = .578), co-workers (r = .512), work environment (r = .522), work itself (r = .616), knowledge (r = .568), attitude (r = .534), and skill (r = .550). Multiple regression analysis indicated five predictors of job satisfaction of officers, namely knowledge, skill, promotion opportunities, work itself, and work environment. The predictor factor described 65.4% variance of job satisfaction of officers. To ensure continuous job satisfaction amongst officers, contributing factors towards satisfaction and dissatisfaction should be given attention by the management. This was because job satisfaction of workers would impact the work performance and the performance of the organisation.